Cognitive and Behavioral Factors Associated With Insomnia in Inpatients With Schizophrenia and Related Psychoses. Issue 10 (October 2015) - Chiu, Vivian W.; Harvey, Robert H.; Sloan, Nancy B.; Ree, Melissa; Lin, Ashleigh; Janca, Aleksandar; Waters, Flavie
Abstract : Abstract: This study examines cognitive and behavioral factors linked to insomnia in individuals with schizophrenia and other psychotic disorders (with and without insomnia) and healthy controls (with and without insomnia). Fifty-five psychiatric inpatients and 66 healthy controls ( n = 25 with insomnia in both groups) completed the Insomnia Severity Index, Thought Control Questionnaire for Insomnia-Revised, Dysfunctional Beliefs and Attitudes about Sleep scale, Sleep Hygiene Knowledge scale, and Beliefs about Causes of Sleep Problems questionnaires. Both insomnia groups demonstrated night-time rumination, aggressive suppression as a thought control strategy, and exaggerated views regarding the health consequences of poor sleep. In addition, the psychiatric group with insomnia frequently reported the causes of insomnia to be related to their illness (rather than to their lifestyle factors) and had an incomplete understanding of good sleep habits. Psychological interventions should be more commonly pursued as a first line of treatment for insomnia in schizophrenia and psychosis, and these should be adapted to address the unique knowledge gaps and cognitive style of patients.